The 2020 Coronavirus Pandemic as a Change-Event in Sport Performers’ Careers: Conceptual and Applied Practice Considerations - Samuel, Roy David; Tenenbaum, Gershon; Galily, Yair (Frontiers in Psychology, 2020)
The Coronavirus experience (CE) presents a highly challenging period for sport performers (e.g., athletes, coaches, referees), with potential effects on their lives and career trajectories. In this article, we initially conceptualize the CE using the scheme of change for sport psychology practice (Samuel and Tenenbaum, 2011a). Within this framework, the CE is understood as a longitudinal, multifaceted, unpredicted, non-controlled change-event, with four distinct stages: (a) a pre-Coronavirus stage with unique career contextual conditions (i.e., stable engagement or a transitional period), (b) Coronavirus stage-A accompanied by instability and confusion, emotional response, and cognitive appraisal, (c) Coronavirus stage-B characterized by active coping or regression, and (d) Coronavirus stage-C; instability endures or decreases, depending on career trajectory. The CE presents sport performers with modifications in various dimensions, including physical and physiological, motor skills, psycho-social and self-identity, relationships, performance and achievement, motivation and aspirations, organizational-occupational, and micro– and macro–cultural issues. Sport performers can exhibit several emotional responses (i.e., positive, negative, neutral), and consequential coping endeavors. The development of the change process is underlined by key decisions, manifested in sport performers’ attempts to implement responsive change in these dimensions (e.g., adapt their diets, sleep routines, and exercise regimen). The second part of the article discusses applied practice considerations, presenting various techniques and methodologies which practitioners can apply while consulting from a change-based perspective. Ethical issues pertaining to the formation of effective therapeutic relationships during this period are also assessed. The conclusions offer future avenues for researchers and practitioners when attempting to evaluate and cope with this global phenomenon.